Rapid treadmilling of brain microtubules free of microtubule-associated proteins in vitro and its suppression by tau - Panda, Dulal (The National Academy of Sciences, 1999)
We have determined the treadmilling rate of brain microtubules (MTs) free of MT-associated proteins (MAPs) at polymer mass steady state in vitro by using [(3)H]GTP-exchange. We developed buffer conditions that suppressed dynamic instability behavior by ≈10-fold to minimize the contribution of dynamic instability to total tubulin-GTP exchange. The MTs treadmilled rapidly under the suppressed dynamic instability conditions, at a minimum rate of 0.2 μm/min. Thus, rapid treadmilling is an intrinsic property of MAP-free MTs. Further, we show that tau, an axonal stabilizing MAP involved in Alzheimer’s disease, strongly suppresses the treadmilling rate. These results indicate that tau’s function in axons might involve suppression of axonal MT treadmilling. We describe mathematically how treadmilling and dynamic instability are mechanistically distinct MT behaviors. Finally, we present a model that explains how small changes in the critical tubulin subunit concentration at MT minus ends, caused by intrinsic differences in rate constants or regulatory proteins, could produce large changes in the treadmilling rate.